Analysis of urban heat island and flood-prone areas for green space planning. Issue 2 (12th May 2021) - Saiz-Rodríguez, Juan Alejandro; Salazar-Briones, Carlos; Ruiz-Gibert, José Mizael; Moctezuma, Alejandro Mungaray; Lomeli-Banda, Marcelo A.
Abstract : Heat islands and floods have an impact on human life and the environment. In this research study, remote sensing and geographic information systems (GIS) were used to identify the effects of urban heat islands and potential flood zones. The results were used to create a priority attention map for Mexicali, Baja California, as a planning tool for implementing green space projects. The land surface temperature was estimated from Landsat-8 imagery. For flood-prone area estimation and a topographic wetness index, a digital elevation model was processed with a spatial resolution of 5 × 5 m. The results showed the need to incorporate green spaces within the urban area since the inhabitant-green space ratio was 2.43 m 2 . Furthermore, it was observed that more than 60% of green areas do not significantly affect the reduction of heat islands; therefore, the effective ratio of green spaces with a cooling effect per inhabitant was 1.27 m 2 . The implementation of spatial techniques in GIS considering heat islands and potential flood zones has not been traditionally considered in urban planning and cities dynamics in developing countries in arid zones. However, the determination of long-distance conditions in comprehensive planning instruments could be implemented to increase urban areas resilience.